Debt and financial vulnerability on the verge of retirement - Annamaria Lusardi; Olivia S. Mitchell; Noemi Oggero (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
We analyze older individuals' debt and financial vulnerability using data from the Health and Retirement Study (HRS) and the National Financial Capability Study (NFCS). Specifically, in the HRS we examine three different cohorts (individuals age 56-61) in 1992, 2004, and 2010 to evaluate cross-cohort changes in debt over time. We also use two waves of the NFCS (2012 and 2015) to gain additional insights into debt management and older individuals' capacity to shield themselves against shocks. We show that recent cohorts have taken on more debt and face more financial insecurity, mostly due to having purchased more expensive homes with smaller down payments.
urn:nbn:de:hebis:30:3-438608
Keywords: 330